Strategi Pemasaran Produk UMKM Melalui Sertifikasi Halal MUI - Putra, Fadinsi Prima; Kusnawan, Aep; Yulianai, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to find out and understand the product strategy, price strategy, place strategy, promotion strategy, and SWOT analysis on UMKM certified and not certified by MUI halal. The research method used is descriptive method with a qualitative approach. Sources of data were obtained from interviews and documentation studies of the West Java MUI and a number of UMKM certified and not MUI halal certified at Rumah BUMN Bandung. The results showed that of the 15 UMKM fostered by Rumah BUMN Bandung, 10 of them already have a halal certificate and 5 have not been certified halal. From the comparison that has and has not been certified halal, it is known: first, the product strategy, namely the UMKM have carried out the production process of their respective products with good quality, such as the selection of quality basic ingredients and additional ingredients, without preservatives, nutritional value, attractive packaging, and has the brand so that it is easily recognized by consumers, the two pricing strategies, namely the UMKM determine the price according to the cost of goods sold, as for what distinguishes between those who have and those who have not, namely the pricing to target consumers between middle and lower middle class. The third place strategy is that SMEs market their products in strategic places that are visited by many people. The four promotional strategies are that UMKM promote by utilizing social media and exhibition events. The five SWOT analyzes of the application of halal certification to UMKM provide bright prospects in the future.